1988
DOI: 10.1029/gl015i012p01369
|View full text |Cite
|
Sign up to set email alerts
|

An artifact in the measurement of N2O from combustion sources

Abstract: An artifact in the use of sampling containers for the measurement of nitrous oxide emissions from fossil fuel combustion has been identified. The storage of moist combustion products containing SO2 and NO for periods as short as 2 hours can lead to the formation of several hundreds of parts‐per‐million of N2O in the sample containers where none originally existed. The drying of the gas in a 0°C trap before introduction into the container reduces, but does not eliminate N2O formation. Removing SO2 prior to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 5 publications
5
62
0
1
Order By: Relevance
“…The reason the opposite phenomenon was found in these two studies might be a result of air samples for N 2 O measurement being taken without a filter in our study, but the air samples were collected with a potassium chloride-impregnated filter for removal of sulfur dioxide (SO 2 ) in Hayashi et al (2014). Because coexisting SO 2 and nitric oxide (NO) react to form N 2 O during sample storage (Muzio and Kramlich 1988;Linak et al 1990;Preto et al 2004), the N 2 O emissions calculated in our study might be overestimated, even though their contribution to global warming is negligible compared with other gas species (Fig. 5).…”
Section: Discussionmentioning
confidence: 76%
“…The reason the opposite phenomenon was found in these two studies might be a result of air samples for N 2 O measurement being taken without a filter in our study, but the air samples were collected with a potassium chloride-impregnated filter for removal of sulfur dioxide (SO 2 ) in Hayashi et al (2014). Because coexisting SO 2 and nitric oxide (NO) react to form N 2 O during sample storage (Muzio and Kramlich 1988;Linak et al 1990;Preto et al 2004), the N 2 O emissions calculated in our study might be overestimated, even though their contribution to global warming is negligible compared with other gas species (Fig. 5).…”
Section: Discussionmentioning
confidence: 76%
“…During the interim, the gas samples are stored at ambient temperature. Recently, Muzio and Kramlich 15 have shown that these grab samples can undergo chemical reaction within the containers, forming N 2 O concentrations substantially higher than originally formed in the combustion process. This paper will 1) discuss this phenomena including the experimental observations; 2) propose a chemical mechanism; 3) propose measures to minimize this artifact; and 4) discuss the implications of N2O emissions from combustion sources.…”
mentioning
confidence: 99%
“…The international reference method for sampling and determination of N 2 O content in flue gas, ISO 21258 (2000), and the United Nations Framework Convention on Climate Change Clean Development Mechanism (UNFCCC CDM) methodology (2010) specify the use of NDIR technique. However, the literature data suggest that grab samples containing NO, SO 2 , and condensed H 2 O produce N 2 O as an artifact (Muzio and Kramlich, 1988;Montgomery et al, 1989;Muzio et al, 1989). As a result, the N 2 O levels reported may be higher than the levels actually produced directly by combustion systems.…”
Section: Ftir Versus Ndirmentioning
confidence: 41%